IMPLEMENTATION OF BANKING PRINCIPLES OF CAUTION IN LIQUIDATION OF DEPOSITS BELONGING TO HEIRS BY THE RELATED HEIRS DEED OF CONFIRMATION OF INHERITANCE DECLARATION MADE BY A NOTARY (STUDY AT MANDIRI BRANCH OFFICE, MALANG REGENCY) - Alief Pratama Romadhon; Suhariningsih; Fathul Laila (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The abstract serves as a concise summary of your research paper, highlighting the essential components that provide readers with an overview of your work. It should effectively capture the key issues addressed, the primary objectives of the study, the methods utilized, and the significant results achieved. This summary must be written in a single cohesive paragraph, limited to a maximum of 200 words. Ensure to follow the formatting specifications: use Times New Roman font, size 11, with single spacing, and present it in italics. The goal is to engage the reader while successfully conveying the importance and impact of your findings.